Atorvastatin inhibits neuronal apoptosis via activating cAMP/PKA/p‐CREB/BDNF pathway in hypoxic‐ischemic neonatal rats. Issue 4 (18th March 2022) - Yu, Luting; Liu, Shixi; Zhou, Ruixi; Sun, Hao; Su, Xiaojuan; Liu, Qian; Li, Shiping; Ying, Junjie; Zhao, Fengyan; Mu, Dezhi; Qu, Yi
Abstract: Neuronal apoptosis is one of the main pathological processes of hypoxic‐ischemic brain damage (HIBD) and is involved in the development of hypoxic‐ischemic encephalopathy (HIE) in neonates. Atorvastatin has been found to have neuroprotective effects in some nervous system diseases, but its role in regulating the pathogenesis of neonatal HIBD remains elusive. Thus, this study aimed to explore the effects and related mechanisms of atorvastatin on the regulation of neuronal apoptosis after HIBD in newborn rats. The rat HIBD model and the neuronal oxygen glucose deprivation (OGD) model were established routinely. Atorvastatin, cAMP inhibitor (SQ22536), and BDNF inhibitor (ANA‐12) were used to treat HIBD rats and OGD neurons. Cerebral infarction, learning and memory ability, cAMP/PKA/p‐CREB/BDNF signaling molecules, and apoptosis‐related indicators (TUNEL, cleaved caspase‐3, and Bax/Bcl2) were then examined. In vivo, atorvastatin reduced cerebral infarction, improved learning and memory ability, decreased the number of TUNEL‐positive neurons, inhibited the expression of cleaved caspase‐3 and Bax/Bcl2, and activated the cAMP/PKA/p‐CREB/BDNF pathway in the cerebral cortex after HIBD. In vitro, atorvastatin also decreased the apoptosis‐related indicators and activated the cAMP/PKA/p‐CREB/BDNF pathway in neurons after OGD. Furthermore, inhibition of cAMP or BDNF attenuated the effect of atorvastatin on the reduction of neuronal apoptosis, suggesting that atorvastatin inhibits HIBD‐induced neuronal apoptosis and alleviates brain injury in neonatal rats mainly by activating the cAMP/PKA/p‐CREB/BDNF pathway. In conclusion, atorvastatin may be developed as a potential drug for the treatment of neonatal HIE.